2012
DOI: 10.1111/1477-9552.12010
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Valuation of Alternative Meat Origin Labels

Abstract: Abstract:Results from a split-sample survey of the U.S. population reveal consumers prefer meat products carrying origin information to unlabeled alternatives. Consumers are largely unaware of origin labeling laws and are indifferent to an important aspect of the implementation of current mandatory country of origin information rules in the U.S. In particular, consumers value meat products labeled "Product of North America" approximately the same as "Product of UnitedStates." Despite the similarity of these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 22 publications
1
24
1
Order By: Relevance
“…This last finding differs from the one obtained by Tonsor et al . () for meat who found that consumers value meat produced in the country (US) approximately the same as meat produced in North America (Canada, Mexico and US).…”
Section: Estimation and Resultsmentioning
confidence: 99%
“…This last finding differs from the one obtained by Tonsor et al . () for meat who found that consumers value meat produced in the country (US) approximately the same as meat produced in North America (Canada, Mexico and US).…”
Section: Estimation and Resultsmentioning
confidence: 99%
“…Essentially, origin information contributes to food choices, consumer knowledge and perceptions of quality (Deselnicu et al ., ; Bonroy and Constantatos, ). Such beliefs and resulting expectations may exist even when consumers are largely unaware of origin labelling laws (Tonsor et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In developed countries, both environmental awareness and consumer awareness of healthy and safe food has increased in the last three decades, leading to a significant increase in the demand for safe organic [23][24][25][26][27] products, including those that are pesticide-free, or pesticide residue-reduced [28][29][30][31][32][33] as well as products from a particular origin [34][35][36][37]. While consumer awareness has received considerable research attention in Asia [26,[38][39][40][41], little has occurred in African countries, with just a sweet pepper, tomato, amaranths, gboma and basilica.…”
Section: Introductionmentioning
confidence: 99%